50.1k views
0 votes
Simplify

Complete the chart.
Original
Function
Rewrite
Differentiate
(Power Rule)
2
3) y =
6
3x
4) y = Vx7

Simplify Complete the chart. Original Function Rewrite Differentiate (Power Rule) 2 3) y-example-1

1 Answer

9 votes

Answer:

Explanation:

Original Function Rewrite Differentiate Simplify

3). y =
(2)/(3x^6) y =
(2)/(3)x^(-6) y' =
(2)/(3)(-6)x^((-6-1)) y' =
-(4)/(x^(7))

4). y =
\sqrt[4]{x^7} y =
x^{(7)/(4)} y' =
(7)/(4)x^{((7)/(4)-1)} y' =
(7)/(4)x^{(3)/(4)}

User Daniel Richter
by
5.6k points